Daily Report - Kendal District Strike Committee, 3 May 1926 (page 2)
1926-05-03 "Daily Report - Kendal District Strike Committee, 3 May 1926 (page 2)" [g0085002.jpg], 3 May 1926, Kendal District Strike Committee